1999
DOI: 10.1017/s1357729800050505
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the proportion of Duroc genes on growth, carcass and pork eating quality characteristics

Abstract: A study was carried out involving 721 pigs, comprising boars and gilts, with either 0, 0.25 , or 0.50 Duroc inclusion level, which were produced by mating Large White boars with Large White × British Landrace sows, Large White boars with Duroc × (Large White × British Landrace) sows, or Duroc boars with Large White × British Landrace sows, respectively. Animals were reared on one of seven different feeding regimens from 30 to 90 kg live weight. Tissue growth rates were determined using a triple sampling proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
3
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
8
38
3
3
Order By: Relevance
“…Progeny of LW sires had the leanest bellies and the highest LBP. Results comparing DU with LW for carcase weight and back fat in this study are consistent with breed contrasts for average daily gain and carcase fat reported in other studies (Johnson and Goodwin, 1995;Blanchard et al, 1999c). There was no comparable literature available for progeny of LR or DS sires.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Progeny of LW sires had the leanest bellies and the highest LBP. Results comparing DU with LW for carcase weight and back fat in this study are consistent with breed contrasts for average daily gain and carcase fat reported in other studies (Johnson and Goodwin, 1995;Blanchard et al, 1999c). There was no comparable literature available for progeny of LR or DS sires.…”
Section: Resultssupporting
confidence: 88%
“…In our study, meat from the faster growing females was no tenderer than meat from their male contemporaries, although females did have higher IMF and reduced CL. The study of Blanchard et al (1999c) also demonstrated that progeny of purebred Duroc sires had higher IMF levels and improved eating quality, but carcases were fatter, similar to the results found in this study. Slaughter progeny containing only 25% Duroc genes had IMF levels, marbling scores and subcutaneous fat levels more similar to progeny of LW (0% Duroc) than DU (50% Duroc) boars, implying that a 50% Duroc inclusion is required to obtain demonstrable differences between Duroc-infused sire breeds in meat and eating quality traits.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Having in mind maintenance of good quality slaughter material, each new fattener genotype obtained should be examined (1)(2)(3)(4)(5)(6). Quantitative and qualitative features of meat tissue determine consumption and technological usefulness of pork meat (1,7).…”
Section: Introductionmentioning
confidence: 99%
“…Having in mind maintenance of good quality slaughter material, each new fattener genotype obtained should be examined (1)(2)(3)(4)(5)(6). Quantitative and qualitative features of meat tissue determine consumption and technological usefulness of pork meat (1,7). The aim of this study was an assessment of the indices characterizing the longissimus lumborum muscle in fatteners that were the product of an application of various variants of commodity crossbreeding using 2 Polish and 2 foreign breeds.…”
Section: Introductionmentioning
confidence: 99%